Effect on heart rate and blood pressure after mental stress in coronary artery disease patients and normal individuals - Shrestha, Esha; Shrestha, Shreesh; Pramanik, Tapas; Singh, Smriti (Journal of Physiological Society of Nepal, 2021)
Introduction: Cardiovascular diseases are the leading cause of death in almost every region of the world. One of the major risk factors for coronary artery disease is stress. The study was carried out to find the effect of mental stress on heart rate and blood pressure in coronary artery disease patients and in their age-matched normal counterparts. Materials and methods: Blood pressure and heart rate were recorded before and immediately after standardized mental stress (mental calculation for a minute) after necessary instruction among the volunteers (n=100, 50 coronary artery disease patients and 50 control, age 40-80 years) and then analyzed. Results: The mean HR was 75.40/min and the mean SBP was 121.84 mmHg of patient before stress which increased to 80.26/min (HR) and 135.12 mmHg (SBP) after stress. Similarly, the mean HR was 76.72/min and SBP was 116.24 mmHg before stress which increased to 80.5/min (HR) and 121.56 mmHg (SBP) after stress in normal individual. The result of the study showed mental stress induced rise in heart rate and blood pressure in both the groups. Nevertheless, mental stress induced increase in systolic blood pressure in patients exhibited higher than that of their aged-matched normal counterparts (p<0.05). Conclusions: The incidence of coronary artery disease is increasing day by day in the modern society. The measurement of heart rate and blood pressure (casual and mental stress induced) may help the clinicians to predict/screen coronary artery disease, especially the silent ones, and can prevent sudden angina pain.